The Experiences of patients with end stage renal disease living on haemodialysis - Lau, Sie Ngo (Universiti Malaysia Sarawak (UNIMAS), 2014)
Haemodialysis is used as a life-sustaining therapy for patients suffering from End-stage Renal Disease (ESRD). The disease and haemodialysis (HD) treatment affect an individual physically, psychologically, emotionally, socially, financially and spiritually. This study utilized a qualitative, exploratory and descriptive method with face-to-face in-depth interview to explore the experiences of patients with ESRD living on HD treatment in Kuching, Sarawak, Malaysia. Applying purposive and snowball sampling method, a total of 28 patients from four HD centers participated in this study. Data were transcribed verbatim and analyzed using the 9-steps interpretive thematic analysis method adopted from Zabidah (2010). Four major themes emerged: (1) Living with the paradox, (2) When life is dependent on haemodialysis, (3) Adapting into new life with haemodialysis and (4) A sense of hope in the unknown future. HD caused dependency on HD; physical limitations; restricted life; loss of freedom; employment challenges; financial difficulties; vascular access related problems; psychological distress and change of family roles and responsibilities. Patients are waiting and hoping for kidney transplants, freedom to live, restore good health, attain pre dialysis status, live healthy, and employment as mean of hopes. This study has identified gaps in the delivery of psychological care; rehabilitation in employment; spiritual, moral and emotional support in addressing the holistic nursing care toward patients on HD. Therefore, it is suggested that a more structured psychological care and financial assistance, rehabilitation in employment, spiritual, moral and emotional support be provided to patients, as well as family. Future research should explore more about the employment challenges or factor that contribute to job retention or unemployment among patients living with HD in depth.